Entomofauna de potencial interesse forense médico-legal em dois ambientes de área rural de Uberlândia-MG - Faria, Lucas Silva de (2013)
Studies on the diversity and biology of insects colonizing animal carcasses and human corpses decaying, have gradually increased and contributed to the development of forensic entomology in Brazil. These information associated with the various abiotic factors and environmental conditions of each region, can help in determining the postmortem interval (PMI) and obtain other information of importance in forensic medicine. This work aims to obtain data on the insect fauna of potential forensic interest in two different environments of a rural area during two seasons prevailing in Uberlândia-MG. The two environments studied were a pasture and fragment of semideciduous forest. Samples were collected during the dry and rainy seasons of 2010. The study emphasizes the diversity, relative abundance of species and entomological succession along the decomposition of pig carcasses (Sus scrofa L.) exposed in each environment and season. Eight pig carcasses (10±2 kg) were used in the experiment and adult and immature insects that were present in the traps were collected along the decomposition process of carcasses. A total of 92.489 adult insects were collected in traps and 32.577 insects emerged in the laboratory from immature forms collected. Among the insects attracted, the order Diptera was the most abundant (92,22%), followed by Coleoptera (4,40%), Hemiptera (1,92%), Lepidoptera (0,91%) and Hymenoptera (0,55%). Diptera and Coleoptera were the main groups considered of forensic importance by the large number of species that used the carcasses as breeding substrate. Several of these species are considered potential indicators of PMI as Chrysomya albiceps, Chrysomya putoria, Hemilucilia segmentaria, Ophyra aenescens, Peckia (Pattonella) intermutans, Hermetia illuscens, Dermestes maculates and Necrobia rufipes. The pig carcasses attracted a wide variety of insects and several species were considered potential indicators of environment and seasonality.